Assessment of Enterococcus hirae strain LAB3 isolated from Asian seabass, Lates calcarifer (Bloch, 1970) as probiotic against Vibrio harveyi infection - Masduki, Nur Fathiah (2018)
Seabass farming is one of significant important contributors to the annual world aquaculture production including Malaysia. However, vibriosis has been one of the main diseases problems often cause high mortality and reducing the production. Probiotics are now become subject of interest as new alternative in preventing vibriosis in fish farming culture. This study was undertaken to discover new potential probiotics strain from the group of lactic acid bacteria (LAB) isolated from seabass (Lates calcarifer). Seven potential of LABs were successfully isolated from the intestine and liver of 15 healthy seabass. In in vitro screening test using series of plate assays, co-culture assay and pathogenicity test on TCBS agar, one isolate was showed potential as probiotics. The potential probiont was identified as Enterococcus hirae (LAB3) using 16S rRNA. This strain able to grow at pH 2 to 10 with the best growth at pH 7 within 3 h incubation period and grew best at 4% of NaCl in de Man Rogosa and Sharp (MRS) broth. Antibiotic susceptibility test revealed that, this strain was resistant to: kanamycin, penincilin, gentamycin, tetracycline and streptomycin as well as able to secrete lipase enzyme. In addition, this strain was able to produce biofilm up to 30 h of incubation period. In a preliminary in vivo assay using Artemia salina, result demonstrated a significant survival of Artemia treated with E. hirae LAB3 at 106 CFUmL-1 and challenged with V. harveyi (70.00±3.06%) compared to the control Artemia with pathogen only (V. harveyi 13.33±1.45%). This strain was proven able to recude the number of Vibrios load in both Artemia and culture water. Similar results were observed using seabass larvae as a host. Larvae treated with E. hirae LAB3 at 106 CFUmL-1 had significant high survival after challenged with the pathogen V. harveyi (68.33±0.88%) compared with group with pathogen only (V. harveyi 16.67± 3.33%). Vibrios counts were significantly lower in larvae and culture water treated with E. hirae LAB3 at the end of challenged assay. In term of growth rate, larvae treated with E. hirae LAB3 at concentration of 106 CFUmL-1 showed slightly higher but with no significant different in term of growth rate and length increment compared with control without probiotic added. This study suggests that E. hirae LAB3 has potential to be one of the probiotic candidates in aquaculture industry specifically for seabass hatchery system.